Early Palliative Care Reduces End‐of‐Life Intensive Care Unit (ICU) Use but Not ICU Course in Patients with Advanced Cancer - Romano, Andrew M. (Oncologist, 2017)
BACKGROUND. Early palliative care for advanced cancer patients improves quality of life and survival, but less is known about its effect on intensive care unit (ICU) use at the end of life. This analysis assessed the effect of a comprehensive early palliative care program on ICU use and other outcomes among patients with advanced cancer. PATIENTS AND METHODS. A retrospective cohort of patients with advanced cancer enrolled in an early palliative care program (n = 275) was compared with a concurrent control group of patients receiving standard care (n = 195) during the same time period by using multivariable logistic regression analysis. The multidisciplinary outpatient palliative care program used early end‐of‐life care planning, weekly interdisciplinary meetings to discuss patient status, and patient‐reported outcomes assessment integrated within the electronic health record. RESULTS. Patients in the control group had statistically significantly higher likelihood of ICU admission at the end of life (odds ratios [ORs]: last 6 months, 3.07; last month, 3.59; terminal admission, 4.69), higher likelihood of death in the hospital (OR, 4.14) or ICU (OR, 5.57), and lower likelihood of hospice enrollment (OR, 0.13). Use of chemotherapy or radiation did not significantly differ between groups, nor did length of ICU stay, code status, ICU procedures (other than cardiopulmonary resuscitation), disposition location, and outcomes after ICU admission. CONCLUSION. Early palliative care significantly reduced ICU use at the end of life but did not change ICU events. This study supports early initiation of palliative care for advanced cancer patients before hospitalizations and intensive care. IMPLICATIONS FOR PRACTICE. Palliative care has shown clear benefit in quality of life and survival in advanced cancer patients, but less is known about its effect on intensive care. This retrospective cohort study at a university hospital showed that in the last 6 months of life, palliative care significantly reduced intensive care unit (ICU) and hospital admissions, reduced deaths in the hospital, and increased hospice enrollment. It did not, however, change patients’ experiences within the ICU, such as number of procedures, code status, length of stay, or disposition. The findings further support that palliative care exerts its benefit before, rather than during, the ICU setting.